2021
DOI: 10.1109/tcsi.2021.3104644
|View full text |Cite
|
Sign up to set email alerts
|

A High-Level Modeling Framework for Estimating Hardware Metrics of CNN Accelerators

Abstract: GPUs became the reference platform for both training and inference phases of Convolutional Neural Networks (CNN) due to their tailored architecture to the CNN operators. However, GPUs are power-hungry architectures. A path to enable the deployment of CNNs in energy-constrained devices is adopting hardware accelerators for the inference phase. The design space exploration of CNNs using standard approaches, such as RTL, is limited due to their complexity. Thus, designers need frameworks enabling design space exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In [4], Juracy et al reported that a path to enable the deployment of CNNs in energy-constrained devices is adopting hardware accelerators for the inference phase. The authors propose a framework to explore CNNs design space, providing Digital Object Identifier 10.1109/TCSI.2021.3115924 power, performance, and area (PPA) estimations using the system simulator front-end, TensorFlow.…”
mentioning
confidence: 99%
“…In [4], Juracy et al reported that a path to enable the deployment of CNNs in energy-constrained devices is adopting hardware accelerators for the inference phase. The authors propose a framework to explore CNNs design space, providing Digital Object Identifier 10.1109/TCSI.2021.3115924 power, performance, and area (PPA) estimations using the system simulator front-end, TensorFlow.…”
mentioning
confidence: 99%